REPRODUKSI SEHAT, ANEMIA HILANG: Program Edukasi Terpadu bagi Siswa SMA - fitria, kheli; Nafratilova, Mercy; Hermansyah, Hermansyah (Poltekkes Kemenkes Bengkulu, 2025)
Teenage girls are a vulnerable group in terms of reproductive health and anaemia. Lack of knowledge and misinformation can lead to long-term consequences for adolescent health. This community service activity aims to increase adolescents' knowledge and awareness of reproductive health and how to prevent anaemia in teenage girls. The activity was carried out in the form of interactive dialogue sessions for 52 students at SMA Negeri 1 Kota Bengkulu. The activity involved lectures, discussions, and digital quizzes via the Quiziz platform, accompanied by the distribution of iron tablets. Evaluation results showed that participants were engaged in the activity and could answer questions related to the material correctly. This session proved effective as an interactive learning tool to enhance teenagers' knowledge about the importance of maintaining reproductive health and preventing anaemia. By providing accurate and comprehensive information, teenagers can make better decisions regarding their health.